Demand for DNA probe testing in three genetic centres in Britain (August 1986 to July 1987). Issue 4 (April 1989) - Rona, R J; Swan, A V; Beech, R; Prentice, L; Reynolds, A; Wilson, O; Mole, G; Vadera, P
Abstract : We report a preliminary analysis of the data collected during the first year of the evaluation of clinical genetics in the context of DNA probes in three genetic centres, to show the pattern of the demand for genetic services in the three centres and the services used in meeting that demand. The analysis includes information on 10, 185 persons from 2852 families. The results are presented according to mode of inheritance and according to the most common disorders for which DNA probes have been used in the three centres. The results indicate that the use of DNA probes is now a major element of activity in genetic departments, and that as long as indirect DNA probe testing is the predominant manner of using recombinant technology, the clinical input will be an important element of the costs, probably more so than that of the DNA laboratories, as a large number of family members needs to be tested. In most cases centres have concentrated activity on DNA testing for common and severe genetic disorders. However, there are disorders, such as familial hypercholesterolaemia, which have not been part of the established pattern of services. Conversely, a relatively high number of families have been studied for some disorders of very low incidence. This suggests that the number of DNA laboratories should be limited. The precise arrangements will need to be established. With such services the distribution of DNA testing facilities for different disorders can be controlled to limit duplication. The model followed in Scotland based on collaboration between centres is worth considering. We have detected very large differences in take up rate of services within and between regions. Although many factors may contribute to these differences, ease of access and lay and professional awareness are probably the most important. This is supported by the fact that more patients from the same or neighbouring DHAs attend the genetic centre than from those further away. We also concluded that published guidelines for clinicians in general on the uses of DNA probes, the type of families that could benefit, and the centres to which referrals should be sent would be very useful in increasing coverage and maximising the effectiveness of the services. Since this may increase demand, this educative tool should be coordinated and agreed by the Departments of Health with all the genetic departments and centres in the country.